Crashworthiness Assessment of Carbon/Glass Epoxy Hybrid Composite Tubes Subjected to Axial Loads - Farokhi Nejad, Ali; Koloor, Seyd Saied Rahimian; Arifin, Mohd Luqman Hakim; Shafiei, Ali; Hassan, Shukur Abu; Yahya, Mohd Yazid (Polymers, 2022)
The crashworthiness of composite tubes is widely examined for various types of FRP composites. However, the use of hybrid composites potentially enhances the material characteristics under impact loading. In this regard, this study used a combination of unidirectional glass-carbon fibre reinforced epoxy resin as the hybrid composite tube fabricated by the pultrusion method. Five tubes with different length aspect ratios were fabricated and tested, in which the results demonstrate "how structural energy absorption affects by increasing the length of tubes". Crash force efficiency was used as the criterion to show that the selected L/D are acceptable of crash resistance with 95% efficiency. Different chamfering shapes as the trigger mechanism were applied to the tubes and the triggering effect was examined to understand the impact capacity of different tubes. A finite element model was developed to evaluate different crashworthiness indicators of the test. The results were validated through a good agreement between experimental and numerical simulations. The experimental and numerical results show that hybrid glass/carbon tubes accomplish an average 25.34 kJ/kg specific energy absorption, average 1.43 kJ energy absorption, average 32.43 kN maximum peak load, and average 96.67% crash force efficiency under quasi-static axial loading. The results show that selecting the optimum trigger mechanism causes progressive collapse and increases the specific energy absorption by more than 35%.
Keywords: composite tube; axial load; finite element model; energy absorption; crashworthiness; hybrid composites